Perlindungan Hukum Pejabat Pembuat Akta Tanah (PPAT) terhadap Tindakan Pemalsuan Data pada Akta Jual Beli oleh Penghadap - Reza Sri Maulani; Ismansyah Ismansyah; Syofiarti Syofiarti (LPPM Universitas Ekasakti Padang, 2023)
Land Deed Making Officer is a general official who is authorized to make authentic deeds regarding certain legal deeds regarding land rights or property rights to flats. One of the deeds made by the Land Deed Maker Officer is the sale and purchase deed. In making a sale and purchase deed, it is not uncommon to be disputed by parties or other third parties who feel aggrieved by the deed because of alleged falsification of data on the deed, causing the Land Deed Making Officer to be involved in the matter and be examined by the authorities. In this study, the formulation of problems related to the legal protection of Land Deed Making Officials the act of falsifying data on the sale and purchase deed by the face is : 1. What is the form of legal protection of the Land Deed Making Officer against the act of falsifying data on the sale and purchase deed by the facer? 2. What are the legal consequences of the sale and purchase deed made by the Land Deed Making Officer in which there is data falsified by the face? This research uses a juridical-empirical approach method. The results of the study found that: 1. Legal protection of Land Deed Making Officials against the act of falsifying data on the sale and purchase deed by the face in the form of providing legal assistance carried out by the Ministry, Board of Trustees and Supervisors of Land Deed Making Officials in the form of advice, assistance in investigations and / or expert statements in court both as witnesses and suspects. 2. The legal consequences of the sale and purchase deed in which there is falsified data are sales and purchase deeds that are proven to be legally defective due to non-fulfillment of the legal conditions of the agreement and / or non-fulfillment of the formal and material conditions for making the deed, so that the position of the sale and purchase deed as an authentic deed is canceled or declared null and void to have no binding legal force.